Pengungkapan Corporate Social Responsibility, Mekanisme Good Corporate Governance dan Nilai Perusahaan - Dewi, Gusti Ayu Intan Puspita; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2021)
This study aims to examine the effect of corporate social responsibility disclosure and good corporate governance mechanisms on firm value. Elements of the good corporate governance mechanism are proxied into audit committees, independent commissioners, institutional ownership, and managerial ownership. The tests were carried out on mining companies listed on the Indonesia Stock Exchange in 2016-2019. The sample was selected using purposive sampling technique. Data were analyzed using multiple linear regression analysis. The results show that the more companies increase the disclosure of corporate social responsibility, the impact on increasing the value of the company. Maximizing the function of the audit committee, institutional ownership, and managerial ownership can increase firm value. However, maximizing the function of independent commissioners has no effect on increasing firm value. Keywords : Corporate social responsibility ; Good corporate governance; Firm Value.